Merumuskan Etis Pesan Dakwah Bagi Kreator Konten Dakwah Tiktok - Mahdaniar, Fenny (STID Al-Hadid, 2024)
TikTok as new media in preaching has been widely studied for its effectiveness. Nowadays, there’s many preaching content creators on TikTok, especially young millennial preachers. However, along with that, besides being positive in the development of Islamic da'wah, it has challenges related to ethics, likely delivering da'wah messages. This study expected to be an additional consideration for TikTok da'wah content creators in delivering their da'wah messages, so that preaching on TikTok can be more mashlahat and strengthen the Islam’s image as rahmatan lil 'Alamin. This research method is philosophical-normative, with descriptive-analytic-prescriptive approach. The findings of ethical rules consider characteristics of TikTok users who dominated by millennials and gen-Z that has charateristic’s global thinking, creative, critical, instantaneous. Some of the ethical rules formulated include: the content of da'wah video should be argumentative, based on rational facts, current empirical, accompanied by Islamic arguments that can be traced by digital sources. Addition’s audio soundtrack should be supportive with da'wah message, not merely viral. Delivery of da'wah video content with the format of humor, parody, drama or impersonation other preachers, shouldn’t be excessive which can drop credibility of the impersonated preacher. Stitches/reposts should include content links and anticipate the spread of hoaxes.